2022
DOI: 10.3390/nu14030451
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal mTOR Dysregulation and Morphological Changes in Male Rats after Fetal Growth Restriction

Abstract: Fetal growth restriction (FGR) has been linked to long-term neurocognitive impairment, especially in males. To determine possible underlying mechanisms, we examined hippocampal cellular composition and mTOR signaling of male rat FGR offspring during main brain growth and development (postnatal days (PND) 1 and 12). FGR was either induced by a low-protein diet throughout pregnancy, experimental placental insufficiency by bilateral uterine vessel ligation or intrauterine stress by “sham” operation. Offspring aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…33 Krishna et al also reported that a modest association between birth weight and cognitive ability in later life was observed from a systematic review. 34 The detailed mechanism underlying such association between conditions at birth and later life cognitive function remains largely unexplored; however, several possible mechanisms can be proposed: (i) alteration of the prenatal brain environment could rewire the brain structure and impact on later-life cognitive abilities 35 ; (ii) dysregulation of hippocampal cell proliferation and mammalian target of rapamycin (mTOR) signaling was reported by Schomig et al 36 (however, mTOR activation varied in different ways depending on the cause of IUGR); (iii) an earlier life-induced propensity toward diseases such as hypertension or diabetes mellitus may facilitate age-related dementia possibly via vascular dysfunction; and (iv) alteration of IGF-1 level, which was previously associated with dementia risk, particularly for Alzheimer's disease, might be provoked by earlier life abnormalities or IUGR. 33,37 IGF-1 also plays an essential role in skeletal muscle morphogenesis and maturation.…”
Section: Dementia and Developmental Origins Of Health And Diseasementioning
confidence: 99%
“…33 Krishna et al also reported that a modest association between birth weight and cognitive ability in later life was observed from a systematic review. 34 The detailed mechanism underlying such association between conditions at birth and later life cognitive function remains largely unexplored; however, several possible mechanisms can be proposed: (i) alteration of the prenatal brain environment could rewire the brain structure and impact on later-life cognitive abilities 35 ; (ii) dysregulation of hippocampal cell proliferation and mammalian target of rapamycin (mTOR) signaling was reported by Schomig et al 36 (however, mTOR activation varied in different ways depending on the cause of IUGR); (iii) an earlier life-induced propensity toward diseases such as hypertension or diabetes mellitus may facilitate age-related dementia possibly via vascular dysfunction; and (iv) alteration of IGF-1 level, which was previously associated with dementia risk, particularly for Alzheimer's disease, might be provoked by earlier life abnormalities or IUGR. 33,37 IGF-1 also plays an essential role in skeletal muscle morphogenesis and maturation.…”
Section: Dementia and Developmental Origins Of Health And Diseasementioning
confidence: 99%